Long-term differences in fertilisation type change the bacteria:archaea:fungi ratios and reveal a heterogeneous response of the soil microbial ionome in a Haplic Luvisol. (February 2023) - Schwalb, Sanja A.; Li, Shiwei; Hemkemeyer, Michael; Heinze, Stefanie; Joergensen, Rainer Georg; Mayer, Jochen; Mäder, Paul; Wichern, Florian
Abstract: Organic farm management through farmyard manure application is associated with soil organic carbon sequestration facilitated by more balanced nutrient stoichiometry of macro- and micronutrients. Quantitative information on micronutrients within the soil microbial biomass is lacking. Using soils from a 40-year old long-term field trial (DOK), we investigated if fertilisation differences (farmyard manure equivalent to 0.7 or 1.4 livestock units per hectare and mineral fertilisation) and farm management (biodynamic, organic, conventional) changed the soil microbial ionome and stoichiometry and if this is related to microbial community shifts. Soil (15% sand, 70% silt and 15% clay) from the top 20 cm was analysed for microbial biomass carbon, nitrogen and phosphorus. Further elements were assessed via an adapted chloroform-fumigation extraction procedure. Abundances of bacteria, archaea, and fungi were determined ( q PCR). Farmyard manure increased microbial biomass by approximately two-fold and the contribution of bacteria and archaea by up to approximately five-fold. Microbial biomass phosphorus and magnesium increased with mineral fertilisation (from 7 to 14 μg g −1 soil) and farmyard manure (from 0.5 to 2.7 μg g −1 soil), respectively. The microbial biomass carbon to potassium ratio remained similar, at around 47:1, revealing stoichiometric control. Microbial biomass manganese was reduced from 3.5 to 2.2 μg g −1 soil with lower availability due to raised pH in biodynamic management. The microbial stoichiometry and ionome were mainly affected by nutrient input and soil chemical properties; direct links between microbial (micronutrient-) stoichiometry and microbial community changes cannot be established with certainty due to potential confounding effects of pH changes. Highlights: Soil microbial biomass K, Mg, Zn, Mn, Cu measured in situ via chloroform-fumigation. Homeostatic (K, Cu) as well as plastic stoichiometry (Mg, Zn, Mn) was found. pH exerted control over available elements which influenced microbial stoichiometry. Farmyard manure increased bacterial and archaeal contribution to community.